The battle of Alzheimer’s Disease – the beginning of the future Unleashing the potential of academic discoveries - Lundkvist, Johan; Halldin, Magnus M.; Sandin, Johan; Nordvall, Gunnar; Forsell, Pontus; Svensson, Samuel; Jansson, Liselotte; Johansson, Gunilla; Winblad, Bengt; Ekstrand, Jonas (Frontiers in Pharmacology, 2014)
Alzheimer Disease (AD) is the most common form of dementia, affecting approximately 36 million people worldwide. To date there is no preventive or curative treatment available for AD, and in absence of major progress in therapeutic development, AD manifests a concrete socioeconomic threat. The awareness of the growing problem of AD is increasing, exemplified by the recent G8 Dementia Summit, a meeting held in order to set the stage and steer the compass for the future. Simultaneously, and paradoxically, we have seen key players in the pharmaceutical industry that have recently closed or significantly decreased their R&D spending on AD and other CNS disorders. Given the pressing need for new treatments in this area, other actors need to step-in and enter this drug discovery arena complementing the industrial efforts, in order to turn biological and technological progress into novel therapeutics. In this article, we present an example of a novel drug discovery initiative that in a non-profit setting, aims to integrate with both preclinical and clinical academic groups and pharmaceutical industry to explore the therapeutic potential of new concepts in patients, using novel biology, state of the art technologies and rapid concept